PERLINDUNGAN HUKUM BAGI PEKERJA LAUNDRY TERHADAP PENULARAN PENYAKIT MELALUI PAKAIAN - Andy Surya Wirawan, I Gst Ngr Bagus; Wiryawan, I Wayan; Dunia, Ngakan Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 05, Juli 2014, 2014)
Laundry worker jobs seem trivial, but it has the risk of contracting various diseasesoutweigh pekerjan-other work. The more widespread the laundry business is notaccompanied by adequate protection for laundry workers. As we know, the dirty clothesdilaundrykan not only come from a healthy person only. Sometimes it also comes from theclothes of someone who is suffering from a particular disease such as influenza, variousskin diseases, typhoid, diarrhea, hepatitis and other infectious diseases. Of Article 86 ofLaw Number 13 Year 2003 concerning Manpower mentioned it is clear that every worker has the right of which is the protection of safety and health in accordance with the rules inthe law but in reality a lot of workers who do not get appropriate protection. The purposeof this study are to determine the form of legal protection laundry businesses for theirlosses due to the transmission of disease through labor laundry clothes.To answer the above problems, the use of empirical legal research by examining thelaws that are secondary data, then linked to the fact the field that information obtainedfrom interviews with informants. Furthermore, the data presented in descriptive qualitative.The results showed the form of legal protection for laundry workers againstinfectious diseases through clothing, at this time only limited use of protective items such asgloves, masks and aprons when in contact with dirty clothes from laundry consumers.However, not all businesses implement a protection system such as this because ofignorance laundry workers and owners.
Keywords: Protection Law, Laundry, Disease Transmission, Workers